The effects of the COVID-19 environments on changes in body composition in Japanese elite fencing athlete - Yasuda, J.; Kondo, E.; Takai, E.; Eda, N.; Azuma, Y.; Motonaga, K.; Dohi, M.; Kamei, A. (Sports, 2021)
The Japanese government declared a state of emergency from 7 April to 25 May to limit people`s movement due to the coronavirus disease (COVID-19) pandemic. This pandemic negatively affects athletes` body composition due to inactivity. Therefore, we compared the body composition data (i.e., fat-free mass (FFM) and fat mass (FM)), of 43 Japanese elite fencers (22 men, 21 women), in September 2019 for baseline, and of 21 (12 men, 9 women) who completed the following measurements in June 2020 (POST; immediately after rescinding the emergency state) and September 2020 (POST-4M; 4-months after rescinding the emergency state). Results at baseline indicate no significant differences in body compositions among fencing disciplines. We also confirmed no significant changes in body mass during the 1-year investigation period in either sex. There were no time-course changes in men`s FFM and FM; however, time-course changes in women`s FM were observed. Compared to the baseline, FM values were significantly higher at POST and then returned to baseline levels at POST-4M in women. In conclusion, the 2-month stay-at-home period due to COVID-19 negatively affected women`s FM changes, but not their FFM or men`s FM.